Hunter to gatherer and back: immunological synapses and kinapses as variations on the theme of amoeboid locomotion. - Dustin, M (2008)
The immunological synapse was initially defined as a stable cell-cell junction composed of three concentric supramolecular activation clusters (SMACs) enriched in particular components: a central SMAC with clustered antigen receptors and kinases, a peripheral SMAC rich in beta2 integrin adhesion molecule LFA-1, and a distal SMAC marked by a critical tyrosine phosphatase. In the past year the SMACs have each been identified with functional modules of amoeboid motility, and the stability of the immunological synapse has been revealed as a reconfiguration of the motile apparatus from an asymmetric hunting mode, a kinapse, to a symmetric gathering mode, the synapse. The genetic control of this process involves actinomyosin regulators PKCtheta and WASp. Crtam is involved in postsynaptic polarity in early kinapses prior to cell division. It is unlikely that the immune system is unique in using symmetrization to stop migration without inactivating motile machinery.